2017
DOI: 10.1111/jocn.13896
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a structured preoperative protocol on day of surgery cancellations

Abstract: Aims and objectives:To evaluate the impact of implementing an evidence-based, structured preoperative protocol on day of surgery cancellations in 13 operative specialties.Background: Surgery cancellations cause unnecessary harm for patients and organisations as many cancellations could be prevented. Preoperative care has developed in recent years, and several preoperative interventions have been introduced. However, the optimal model for organising preoperative care remains unknown. Cancellations are a commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The late cancellation rate in this study of 4·3 per cent is similar to that reported previously from the authors' hospital, which was 4·6–4·7 per cent in 2013–2016 for different types of elective surgical operation. These rates are slightly lower than those reported in earlier publications, where cancellation rates varied between 6 and 15 per cent.…”
Section: Discussionsupporting
confidence: 84%
“…The late cancellation rate in this study of 4·3 per cent is similar to that reported previously from the authors' hospital, which was 4·6–4·7 per cent in 2013–2016 for different types of elective surgical operation. These rates are slightly lower than those reported in earlier publications, where cancellation rates varied between 6 and 15 per cent.…”
Section: Discussionsupporting
confidence: 84%
“…The aim of this study was to measure the financial cost of DOS cancellations in a university hospital's 13 operative specialties after the hospital implemented an evidence based structured preoperative protocol. [9,31] According to the results, DOS cancellations caused a financial loss of nearly a million euros during the nine-month study period. To the best of our knowledge, this is the first academic study to measure the financial costs of surgery cancellations in Finland, and it supports previous estimates of the financial costs of elective surgery cancellations.…”
Section: Discussionmentioning
confidence: 99%
“…The data were linked with DOS cancellation rates and reasons col-lected from an administrative database for surgical patients for the period from September 1, 2015 to May 31, 2016. [9] Costs of cancellations are reported in euros in terms of total waste and savings.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 2 more Smart Citations